“Terms and their expression in Uzbek language” (Eurasian Scientific Herald, 2023)
In linguistics, a word, an in-depth study of its semantic-structural features, the relationship that terminologists represent any phenomenon or process due to the universality of the name, that the term is a double-edged essence, that the word can perform a nominative or determinative function was analyzed.